PERANCANGAN IKLAN TV HIMPUNAN BERSATU TEGUH CUP 3 ON 3 BASKETBALL SUMBAR - HERYWANTO MANDALA P., Dr. Budiwirman, M.Pd. Hendra Afriwan, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2016)
Basketball is a ball sport in groups consisting of two teams of five people each who competes scored a point by inserting the ball into the opponent's basket. To promote HBT Cup Tournament 3 On 3 Basketball Sumbar through the medium of television , so that later the participants and basketball fans can find out about the existence of HBT Cup Tournament 3 On 3 Basketball West Sumatra.Television Advertising is a creative documentation processed which is one of the modern communications media by displaying moving pictures and sound merger. Television Advertising is one medium that is effective , because the delivery of information through television ads more easily attract the attention of the target audience . The concept of the design is the indoor Television Commercials featuring skill players one on one and the theme of